Mapping trends in the research in the area of Education in Biochemistry of SBBq from 2006 to 2016 - Cardoso Ferreira, Carlos Roberto; Lessa Goncalves, Harryson Junio [UNESP] (Soc Brasileira Bioquimica & Biologia Molecular, 2017)
This work aims to survey abstracts presented in the Brazilian Society for Biochemistry and Molecular Biology's Annual Meetings in the years 2006 to 2016 and investigate which trends are presented in the Education in Biochemistry area in Brazil. A total of 193 abstracts were found, indicating that the production in the area has increased considerably since 1979. There was a lack of research related to curriculum and, also, a greater insertion of institutions and works focused on teaching methodologies, however, with research directed to techniques, experiments and evaluation models for different teaching objects. Besides, it is also important to consider the presence of abstracts related to websites and blogs, as well as information and communications technologies - ICT, which allow the construction of virtual learning environments, promote digital accessibility and expand the access to education.
Keywords: Science teaching; Information and Communications Technologies; Teaching methodologies